Impact Organization Culture and Motivation on Entrepreneurship Employees At Shipyard Industry in Batam - Fifi Hariani; Muchlis R Luddin; Mahmuddin Yasin (Journal of International Conference Proceedings (JICP), 2019)
Entrepreneurship is a needed issue for employee at Shipyard Industry in Batam. This is due to termination of employment in the shipyard industry in Batam. The purpose of this study is to conduct a study to determine the effects of organization culture and motivation on entrepreneurship employees. This study used 150 employees at Shipyard Industry in Batam. The results show that organization culture has a significant and positive effect on entrepreneurship employees by 0.345. Motivation also has a significant and positive effect on entrepreneurship employees by 0.685. The implication of the results of this study is expected to create new entrepreneurs and new jobs when there is a termination of employment in the shipyard industry in Batam.